Lecithin retinol acyltransferase as a potential prognostic marker for malignant melanoma - Hassel, Jessica C.; Amann, Philipp M.; Schadendorf, Dirk; Eichmüller, Stefan B.; Nagler, Markus; Bazhin, Alexandr V. (Experimental dermatology, 2013)
Metabolism inside cells differs between cancer and normal cells. Because disturbance of vitamin A metabolism might be important, we investigated expression of the enzymes lecithin retinol acyltransferase (LRAT) and RPE65 by immunohistochemistry in melanoma metastases and melanocytic nevi. Semiquantitative evaluation of this expression revealed downregulated expression of RPE65 in malignant melanoma compared with benign melanocytic nevi (P < 0.001). In contrast, expression of LRAT was not significantly different (P = 0.339). High LRAT expression in melanoma metastases was inversely correlated with patient survival; Kaplan-Meier analysis revealed earlier melanoma-related death (P = 0.003). Expression of LRAT might, therefore, be a prognostic marker of the clinical course of melanoma.
Gesehen am 08.10.2021